2004
DOI: 10.3386/w10837
|View full text |Cite
|
Sign up to set email alerts
|

Job Search and Impatience

Abstract: How does impatience affect job search? More impatient workers search less intensively and set a lower reservation wage. The effect on the exit rate from unemployment is unclear. In this paper we show that, if agents have exponential time preferences, the reservation wage effect dominates for sufficiently patient individuals, so increases in impatience lead to higher exit rates. The opposite is true for agents with hyperbolic time preferences: more impatient workers search less and exit unemployment later. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 26 publications
3
92
0
Order By: Relevance
“…First, our results speak to the presence of selection effects in the evaluation of financial programs. Previous research has found that, in general, more patient individuals have better financial outcomes, since they search longer for a good job (DellaVigna and Paserman, 2005), experience steeper wage growth (Munasinghe and Sicherman, 2006), take up welfare programs earlier (Fang and Silverman, 2006), have higher credit scores, and are less likely to default on their loans (Meier and Sprenger, 2006 The rest of the paper is organized as follows: Section 2 presents the design of the field study and of the choice experiments, Section 3 presents the results, and Section 4 concludes by elaborating on the paper's policy implications.…”
Section: Introductionmentioning
confidence: 99%
“…First, our results speak to the presence of selection effects in the evaluation of financial programs. Previous research has found that, in general, more patient individuals have better financial outcomes, since they search longer for a good job (DellaVigna and Paserman, 2005), experience steeper wage growth (Munasinghe and Sicherman, 2006), take up welfare programs earlier (Fang and Silverman, 2006), have higher credit scores, and are less likely to default on their loans (Meier and Sprenger, 2006 The rest of the paper is organized as follows: Section 2 presents the design of the field study and of the choice experiments, Section 3 presents the results, and Section 4 concludes by elaborating on the paper's policy implications.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of time preferences have been examined on on-the-job searches by the unemployed (DellaVigna and Paserman, 2005) and job-to-job transitions, including internal promotions and external job mobility (Drago, 2006;van Huizen, 2010). In standard economic models of on-the-job searches, under which agents are assumed to discount future costs and benefits exponentially, individuals with higher discount rates tend to be impatient.…”
Section: On-the-job Search and Job-to-job Transitionsmentioning
confidence: 99%
“…Impatience has two inconsistent effects on job search effort and reservation wage decision. While impatient agents are more likely to accept the job offer despite low wages and exit unemployment, they prefer to avoid the immediate costs and defer job search activities (DellaVigna and Paserman, 2005). The effect of impatience on job search varies by the assumption of exponential and hyperbolic time preferences.…”
Section: On-the-job Search and Job-to-job Transitionsmentioning
confidence: 99%
See 2 more Smart Citations